Importância dos mastócitos na patogênese da distrofia muscular de Duchenne em cães Golden Retriever - Martins, Isabela Mancini [UNESP] (2015)
Golden Retriever Muscular Dystrophy (GRMD) is the best natural model of Duchenne muscular dystrophy (DMD) with genotypic and phenotypic manifestations similar the human disease. As in to DMD patients, the progressive proliferation of connective tissue in the endomysium of the muscle fibers is parallel to the clinical course of disease in GRMD animals. Studies indicate the relationship of mast cells with the deposition of fibrous tissue due to the release of mediators that activate fibroblasts. The aim of this study was to evaluate the expression of mast cells and its possible relation with muscle injury and fibrosis in GRMD dogs at different ages. It was used fragments of four skeletal muscle groups (masseter, diaphragm, triceps brachial and biceps femoris) of ten dogs between two and eight months age, six affected and four controls. Samples were processed by usual techniques of histology, stained with hematoxylin-eosin and toluidine blue, to verify the expression of mast cells, and Azan trichrome for evaluation and quantification of fibrous. In all muscle groups of dogs GRMD the infiltration of mast cells increased significantly compared to control group. The average number of mast cells decreased with the age of GRMD dogs. All muscle groups showed a significant increase in the amount of collagenous tissue in the control group. The deposition of fibrous tissue decreased with the age of the animals. Possibly, the increase of mast cell degranulation and mediator release would occur in younger GRMD dogs (2 months), fact that potentiated the increase deposition of fibrous tissue in muscle fibers which was gradually decreasing over time and age of the animals. Other studies are needed to clarify the role of mast cells in the pathogenesis of fibrosis in order to contribute to the development of new therapeutic approaches and improve the life expectancy of humans and dogs affected by muscular dystrophy